2011
DOI: 10.1177/0146167211410574
|View full text |Cite
|
Sign up to set email alerts
|

Racial Identification, Racial Discrimination, and Substance Use Vulnerability Among African American Young Adults

Abstract: Two studies examined racial identity (RI) as a protective factor against substance use cognitions among African American young adults who either envisioned or experienced racial discrimination. In Study 1, participants envisioned a discrimination or nondiscrimination scenario, and then their willingness to use drugs and an indirect measure of substance use were assessed. Discrimination was associated with higher levels of use cognitions among participants with low levels of RI. In Study 2, participants were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
93
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 63 publications
5
93
1
Order By: Relevance
“…For example, ninth-grade African Americans who reported high racial centrality showed no association between perceived racial discrimination and psychological distress reported 2 years later (Sellers et al, 2003). In addition, African American young adults did not report an increase in willingness to use substances following a laboratory-based discriminatory experience if they engaged in a writing task that reaffirmed their racial identity (Stock et al, 2011). Although these findings are promising, conflicting studies have found that some elements of racial identity exacerbate the negative effects of discrimination (Burrow & Ong, 2010;Bynum et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…For example, ninth-grade African Americans who reported high racial centrality showed no association between perceived racial discrimination and psychological distress reported 2 years later (Sellers et al, 2003). In addition, African American young adults did not report an increase in willingness to use substances following a laboratory-based discriminatory experience if they engaged in a writing task that reaffirmed their racial identity (Stock et al, 2011). Although these findings are promising, conflicting studies have found that some elements of racial identity exacerbate the negative effects of discrimination (Burrow & Ong, 2010;Bynum et al, 2007).…”
Section: Discussionmentioning
confidence: 92%
“…Acute exposure to discrimination has been associated with decrements in self-awareness and self-regulation, which has been manifested as increased eating and intentions to use substances, among other outcomes (Inzlicht et al, 2006;Stock et al, 2011). Persistent exposure to discrimination may impair the development of skills in self-regulation that are necessary to regulate smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Another study 13 found that discrimination was prospectively associated with use of substances, such as tobacco, alcohol and other drugs. Additionally, the association between experiences of discrimination and alcohol consumption may be moderated by specific factors, [14][15][16][17] such as supportive parenting, 15 ethnic identity, 14,17 linguistic acculturation and time spent in the United States. 16 Other studies suggest that the association between discrimination and alcohol consumption may be mediated by specific phenomena, such as anger, 15,16 delinquent behaviors, 18 hostility, 15 and anxiety or depression.…”
Section: Introductionmentioning
confidence: 99%